Modelo multicritério para identificação de aplicativos de tradução utilizados na mediação educacional da pessoa surda: uma abordagem participativa - (:unkn) unknown (Universidade Federal Rural do Semi-Árido, 2021)
Social inclusion aims to guarantee students with disabilities access to and permanence in the qualified educational system. Among the people with disabilities included in the Brazilian education system are the deaf, who routinely face the challenge of a system lacking teachers trained in the use of Brazilian Sign Language (LIBRAS) in their academic activities. Assistive technologies (AT) can partially fill this gap, playing a relevant role in the educational process of the deaf person. However, not all of them are completely adequate for the inclusion of the deaf person in the school environment. Thus, identifying which of these technologies are most suitable for this inclusion process is a fundamental factor for an effective inclusion of deaf people in school. Therefore, this study aims to propose a reference model to support the process of choosing applications and/or TA resources from the perspective of educational mediation for the deaf, considering local contexts. The proposed methodology is divided into three stages: (i) conception of the model; (ii) data collection and; (iii) classification of applications. The proposed model was applied to illustrate its operation with students listeners of the Licentiate Course in Letters/Libras at the Federal Rural University of the Semi-Árido (UFERSA) – Caraúbas Campus. The VLIBRAS and HANDTALK applications were classified as "Adequate", PRODEAF as "Poor Adequate" and FALIBRAS as "Inadequate". The sensitivity analysis showed that the classification results obtained are stable. Thus, it is concluded that it is possible to use this multi-criteria reference model to select the applications that are most suitable for use in the educational mediation process of the deaf person, since it proved to be robust and effective after its application with users of this type of technology.
Keywords: Tecnologia Assistiva; Acessibilidade Linguística; Surdez; Análise Multicritério de Apoio à Decisão; PROMSORT; Interdisciplinar